Compliance with International Education Standards (IES 2) in Iraq towards the Adoption of International Accounting Standards - kadhim Al-anbagi, Ahmed Taher; Salman Al-azzawi, Nada; Majeed Al-obaidi, Hasanain Hameed (Opción, 2019)
The purpose of the study is to determine the extent of Iraq’s compliance with Inter- national Accounting Standards (IES2). In the coming years, Iraq will seek to move to IFRS and IPSASs. In order for the transition process to be successful in all aspects of (adoption and implementation), it is necessary to prepare professional accountants who are committed to interna- tional standards of education. The research method is archival method that used secondary information sources with some unorganized interviews to compare ac- counting curricula in Iraq with international accounting curricula, in particular IES. In addition, questionnaire form was used. By comparing, the study found that the percentage of compliance in Iraq with the second standard of accounting education (IES2) is 55%, with some gaps particularly with regard to values and professional ethics, and in identifying the working environment, corporate governance, finan- cial markets, organizational behavior and knowledge of information technology. During the questionnaire, which had 60 views of academics and professionals in the field of accounting to find out their Opinions on the importance of completing the educational requirements contained in the standard IES2 in the Iraqi environment.